Gula Aren: Si Hitam Manis Pembawa Keuntungan dengan Segudang Potensi - Lingawan, Angelita; Nugraha, Dio; Jessica, Earlene; Aprianto, Edwin; Geovanny, Geovanny; Ardhito, Muhammad; Japit, Philbert; Trilaksono*, Teddy (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Palm sugar is one of a well known type of sugar from Indonesia, where back then there are so many people working as a palm sugar farmers as a livelihood for everyday life. Nowadays, people who work as palm sugar farmers is decreasing due to the depletion of palm sugar resources and a shift in the community's perspective on the profession of palm sugar farmers in Pakuon Village. Even though the demand of the palm sugar is increasing both domestically and internationally, given the many benefits offered by the palm sugar. This study aims to improve the welfare of palm sugar farmers in Pakuon Village with the development of aspects of production, marketing, and prospects for products that can be produced from palm sugar. The result is an improvement in the production perspective by increasing security which affects farmers' productivity levels. From the marketing perspective, consignment to stalls and packaging is equipped with a logo and contact number increases its brand awareness. Last but not least, the product itself could be develop into another new product called “klepon”, klepon is one of the most famous traditional food in Indonesia and becoming a trend in Pakuon Village because we are pioneer to introduce klepon in Pakuon Village.